Populist minds think alike?: National identity conceptions and foreign policy preferences of populist leaders - Friedrichs, Gordon (Foreign policy analysis, 2022)
The global wave of populism has recently drawn the attention of foreign policy analysts. Despite significant contributions, we still know little about populist leaders’ conceptions of their nation's identity and how these inform foreign policy preferences. What understanding do populists have regarding what their nation stands for and how high it stands in comparison to others? In this article, I introduce a theoretical model of identity-driven foreign policymaking that examines the national identity conceptions of six populist leaders and their non-populist predecessors via an original quantitative content analysis of foreign policy speeches. The article further assesses whether this identity conception translates into foreign policy preferences for revisionism toward the liberal international order by examining voting behavior in the UN General Assembly. The article contributes to conceptual and methodological approaches in foreign policy analysis to study individuals, as well as provides comparative empirical evidence for what drives populists’ foreign policy thinking.
Literaturverzeichnis: Seite 19-22
Keywords: Vereinte Nationen -- Generalversammlung